Comparison of anal HPV natural history among men by country of residence: Brazil, Mexico, and the United States. Issue 1 (July 2017) - Sudenga, Staci L.; Nyitray, Alan G.; Torres, B. Nelson; Silva, Roberto; Villa, Luisa; Lazcano-Ponce, Eduardo; Abrahamsen, Martha; Baggio, Maria Luiza; Salmeron, Jorge; Quiterio, Manuel; Giuliano, Anna R.
Summary: Objectives: Globally, anal cancer incidence is rare, but is increasing in some world regions. Our objective was to assess differences in anal HPV natural history in three countries. Methods: Men aged 18–70 years were recruited from the US (n = 634), Mexico (n = 665), and Brazil (n = 731). Anal specimens were collected every six-months. HPV genotyping was assessed by Linear Array. Anal HPV prevalence was compared using the Fisher's exact test. HPV infection incidence rates (IR) and 95% confidence intervals (CI) were calculated. Results: Any anal HPV prevalence was highest among men from Brazil (24%) compared to Mexico (15%) and the US (15%). When stratified by sexual history, the prevalence of any HPV among MSM/MSMW was 43%, 37%, and 45% and 9%, 12%, and 10% for MSW from Brazil, Mexico, and US, respectively. Any HPV incidence was significantly higher among men from Brazil compared to US men (IRR = 2.4, 95% CI = 1.7–3.4) and comparable between men from Mexico and the US (IRR = 1.2, 95% CI = 0.8–1.8). Conclusion: Men in Brazil and Mexico often have similar, if not higher incidence of anal HPV compared to men from the U.S., and may benefit from gender neutral HPV vaccine policies. Highlights: Anal cancer incidence is increasing among men and women in the developed world. Any anal HPV prevalence was highest among men from Brazil compared to Mexico and US. 9vHPV incidence was comparable between countries after adjusting for sexual history. Men may benefit from gender neutral HPV vaccine policies.